A demarcation against the paradigm of authenticity: Tension between subalternity and autonomy in Monólogo desde las tinieblas - Carrillo Jara, Daniel (2020)
In this paper, our purpose is an analysis of the stories of Monólogo desde las tinieblas from the Marxist approach. For that reason, the paradigm of authenticity as a central element in the critique of Afro-Peruvian literature (especially in the case of Antonio Gálvez Ronceros) is discussed. On the other hand, we propose the importance of the context of subordination, which is in tension with the processes of insubordination and the search for autonomy, for the aesthetic and ethical sense of the text.